Analisis Program Percepatan Penurunan Stunting di Desa Bakaran Batu Kecamatan Lubuk Pakam - M. Fahrur Rozi; Ayu Fadilah; Salsabila Naqiyyah Melfan; Mustofainal Akhyar; Fitriani Paramitha Gurning (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Stunting is one form of problems that occur during the growth and development of children, which is caused by chronic malnutrition for a long time, the physical impact that can be seen is children who look shorter and thinner than other children of their age. Indonesia is one of the countries where people still suffer from stunting. One of the effects that are clearly visible over a long period of time is a disturbance in physical, intellectual, and mental development. The high rate of stunting in Indonesian toddlers is a difficult thing to control, which will later affect the birth of the next offspring with low weight. To reduce the number of stunting toddlers in Bakaran Batu Village, Lubuk Pakam District, the Stunting Reduction Acceleration Program is implemented. Several programs to accelerate stunting reduction in Bakaran Batu Village, Lubuk Pakam District, namely: Counseling or socialization of stunting and Supplementary Food Provision (PMT). The purpose of this study is to reduce the stunting rate which is quite high in Indonesia, in accordance with government program efforts. This research was conducted by applying qualitative research methods accompanied by an analytical approach. The location of the research was carried out in Bakaran Batu Village, Lubuk Pakam District, Deli Serdang Regency. The results showed that the low stunting rate in Bakaran Batu village, Lubuk Pakam sub-district, namely 2 out of 35 children or around 5.7% experienced stunting. This is in accordance with the government's target in reducing stunting acceleration. Keywords : Program, Acceleration, Stunting Reduction.